The Effect Of Profitability, Leverage, And Company Size On The Tax Management Of Bei Energy Sector Companies In 2022-2024 - Elfriska Jesilia; Theresia Olivia; Yosua Samuel Ramli (JURNAL ECONOMINA, 2026)
This study aims to examine the effect of profitability, leverage, and firm size on tax management in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2022– 2024. Tax management is measured using the Effective Tax Rate (ETR), profitability is measured by Return on Assets (ROA), leverage is measured using the Debt to Equity Ratio (DER), and firm size is measured by the natural logarithm of total assets. This study was conducted due to inconsistencies in the results of previous studies regarding the factors affecting tax management. This research uses a quantitative method with secondary data obtained from the financial statements and annual reports of energy sector companies listed on the IDX for the 2022–2024 period. The sampling technique used was purposive sampling, resulting in 23 companies or 69 research data samples. The data were processed using SPSS version 31 through descriptive statistical analysis, classical assumption tests, and hypothesis testing. The results show that profitability and leverage have an effect on tax management, while firm size has no effect on tax management. Future researchers are suggested to add other variables and expand the sector and research period.